2021
DOI: 10.3897/aiep.51.63319
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of morphological variation between stocks of bluefish, Pomatomus saltatrix (Actinopterygii, Perciformes, Pomatomidae), in the Aegean Sea, Black Sea, and Sea of Marmara

Abstract: The population structure of the bluefish, Pomatomus saltatrix (Linnaeus, 1766), in Turkish waters is scarcely described in the literature. To identify any distinct population units of bluefish, and reaffirm the findings of a previous study, four areas were selected: the Aegean Sea, western Black Sea, eastern Black Sea, and the Sea of Marmara. In this study, truss network morphometrics, meristics, and otolith shape analyses were successfully applied for different population identification of the bluefish. Multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…water temperature, current, also chemical characteristics, e.g. O 2 , water clarity (Shuai et al 2018) (Bal et al 2021), African freshwater fish (Turan et al 2005), and European anchovy (Khan et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…water temperature, current, also chemical characteristics, e.g. O 2 , water clarity (Shuai et al 2018) (Bal et al 2021), African freshwater fish (Turan et al 2005), and European anchovy (Khan et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, fish functional morphological traits were understood to be influenced by physical properties of water, such as flow and temperature within fresh water (Chapman et al 2015, Shuai et al 2018) and salinity differences among marine water habitat (Winans 1984, Vidalis et al 1997, Erdoğan et al 2009). The spatial distribution of fish species was previously investigated in different fish species populations in three different seas in Turkish coastal waters, and most of the studies reported that species from the Black Sea populations were separated from the Marmara, Aegean and the Mediterranean Sea (Turan et al 2006, Yedier & Bostancı 2021, Bal et al 2021.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphometrics data of otolith and scale were standardised for the standard length of C. gibelio to remove the effect of body size using the allometric equation (Lombarte & Lleonart, 1993) Vtrans=VSLmSLb, where V trans is the transformed variable, V is the non‐transformed variable, SL is the standard length of each fish, and SL m is the overall (arithmetic) mean standard length of all fish, and b is the slope of the regression of log V on logSL. The modified morphometrics data of otolith and scale were tested for normality and outliers (Bal et al, 2021). Outliers were removed before the subsequent analyses.…”
Section: Methodsmentioning
confidence: 99%
“…The stock structure can be identified through otolith shape and microchemistry, morphometrics and meristic variables, life‐history parameters, parasites and parentage‐based tagging, and genetic approaches (Begg et al ., 1999; Bose et al ., 2017; Neves et al ., 2020). Several studies recommend the use of more than a single stock identification method for assessing phenotypic heterogeneity between subpopulations and achieving sound conclusions (Bal et al ., 2021; Turan et al ., 2006; Waldman et al ., 1988).…”
Section: Introductionmentioning
confidence: 99%